Design and development of TPACK training modules for Chinese university teachers under the wave of educational informatization - He Sun; Noraini Said; Nur Suhaidah Sukor; Xianjun Dai (Global Academic Excellence, 2025)
This research focuses on the design and development of TPACK training module for Chinese college teachers under the background of education informatization. Based on the ADDIE system teaching design model, this paper designs and develops the teaching objectives, teaching contents, teaching modes, teaching resources and teaching implementation plans of TPACK training module courses. This study not only enriched the TPACK training resources for Chinese college teachers, but also provided sufficient support for the subsequent empirical research on TPACK training for college teachers.